Resistance of Klebsiella Sp. Isolated From Chicken and Cages to Chloramphenicol - Rahmat Hidayat; Fachriyan Hasmi Pasaribu; Sri Mulatsih; Akhmad Arif Amin (Rekayasa, 2023)
Klebsiella bacteria is one of the normal flora in poultry that has developed antibiotic resistance. This is reinforced by reports of the incidence of resistance by Klebsiella bacteria in various countries which is quite high. This study aimed to identify the presence of Klebsiella sp. bacteria in chickens and cages, as well as their resistance status to chloramphenicol in relation to the Minister of Agriculture Regulation No. 14/2017. The series of identification included culture, macroscopic and microscopic observations, biochemical tests, and fermentation tests. Antibiotic resistance tests using chloramphenicol disks referring to the Kirby Bauer method. The identification results showed 6 positive samples from 60 samples taken from chickens and 2 positive samples from 21 samples taken from cages. Resistance testing of 8 Klebsiella sp. isolates showed 6 sensitive, 1 intermediate and 1 resistant isolates to chloramphenicol. This is an indication that the Minister of Agriculture Regulation No. 14/2017 is quite effective in prohibiting the use of chloramphenicol in chicken farms.